Gestión escolar para la prevención de embarazos no deseados en los estudiantes de primero de bachillerato del colegio de bachillerato nacional Saquisili ubicada en el cantón Saquisili en el año lectivo 2014 - 2015 - Iza Cando, Wilma Gabriela (2015)
The objective of this research was create ware mess for teenagers National Saquisilí High School to don’t get pregnancies on early age; this event affects directly to the society. Present we are living in a full liberal world with problems and conflicts these problems affect to the teenagers; actually bad strategies have been fomented to prevent pregnancies on early age. The sexual experimentation on teenagers make to forgetting future consequences about of a fast decision, communication, family love, trust, and a bad sexual education in home and high school are the principal causes those affect to teenagers in the high school life. The research was based on students information and to know and interpret principal problem about sexual life on teenagers in their schools. Research proposal is getting a live experiences documentary and to transmit good information about early pregnancies age, also to create aware on teenagers about sexual life responsibility.